An Exogenous Pre-Storage Melatonin Alleviates Chilling Injury in Some Mango Fruit Cultivars, by Acting on the Enzymatic and Non-Enzymatic Antioxidant System - Renu Bhardwaj; Sunil Pareek; J. Abraham Domínguez-Avila; Gustavo A. Gonzalez-Aguilar; Daniel Valero; Maria Serrano (MDPI AG, 2022)
Melatonin (MT) treatment (100 µM, 2 h) was applied to four mango fruit cultivars ('Langra', 'Chaunsa', 'Dashehari', and 'Gulab Jamun'), before being stored at 5 ± 1 °C for 28 d, in order to alleviate chilling injury (CI). Maximum CI reduction was observed in 'Langra' mangoes, and minimum in 'Gulab Jamun' mangoes. This positive effect on quality preservation was associated with an increased concentration of endogenous MT, which prevented the accumulation of reactive oxygen species (H2O2 and O2·−) and stimulated non-enzymatic antioxidants (total phenolic compounds and total flavonoids), possibly due to higher activity of phenylalanine ammonia lyase and tyrosine ammonia lyase. Increased antioxidant activity was also documented in MT-treated 'Langra' mangoes, according to four different assays (DPPH, TEAC, FRAP, and CUPRAC) and higher activity of six antioxidant enzymes (superoxide dismutase, catalase, peroxidase, ascorbate peroxidase, glutathione reductase, and dehydroascorbate reductase). In contrast, 'Gulab Jamun' mangoes showed minimal or no positive effects on the aforementioned variables in response to the exogenous MT application. 'Chaunsa' and 'Dashehari' mangoes had some intermediate effects on their antioxidant system (enzymatic and non-enzymatic) and alleviation of CI, when treated with exogenous MT. We conclude that exogenous MT exerts a cultivar-dependent stimulating effect on the antioxidant system of mangoes, which results in an increase in the fruits' resistance to low temperature.